Coin migration within the euro area - Franz Seitz; Dietrich Stoyan; Karl-Heinz Tödter (Deutsche Bundesbank, 2009)
This paper analyses how many euro coins outflow from Germany and which composition of coins is to be expected in the long run. To this end, a simple mathematical model is formulated and calibrated for exteuro1 coins. The introduction of the euro coins in 2002 presented a unique opportunity to analyse the cross-border migration and the mixing process of coins in different euro-area countries. Based on research by Stoyan and depending on growth assumptions, the annual outflow of German exteuro1 coins is calculated to lie somewhere between 4% and 5%. In the long run, the ratio of German exteuro1 coins in Germany is likely to converge to around 50%.
Keywords: C61; E41; 330; Euro coins; coin volumes; mixing process